2020
DOI: 10.1111/head.14000
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Medical Residents: A Cross‐Sectional Web‐Based Survey

Abstract: Background Although a common complaint and related to factors frequently present in medical residency such as psychological distress, depression, and anxiety, headache is an issue poorly explored among medical residents. Methods This was a cross‐sectional study enrolling medical residents from all geographic regions of Brazil. We applied an online structured survey with demographic and residency program‐related questions, as well as validated tools to assess burnout, diurnal somnolence, anxiety, depression, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…While burnout has been discussed mainly through a psychosocial lens, it should be noted that COVID-19 infection is associated with increased incidence and worsening of neuropsychiatric conditions such as strokes, headaches, depression, and anxiety, which in itself has been linked to burnout [36][37][38][39][40]. Possible mechanisms of pathogenesis are still being explored, including direct injury, hypoxic injury, and immune dysregulation [36,41].…”
Section: Plos Onementioning
confidence: 99%
“…While burnout has been discussed mainly through a psychosocial lens, it should be noted that COVID-19 infection is associated with increased incidence and worsening of neuropsychiatric conditions such as strokes, headaches, depression, and anxiety, which in itself has been linked to burnout [36][37][38][39][40]. Possible mechanisms of pathogenesis are still being explored, including direct injury, hypoxic injury, and immune dysregulation [36,41].…”
Section: Plos Onementioning
confidence: 99%
“…In a cross-sectional study among the general working population, long working hours were associated with the prevalence of headaches, although the association may depend on a lack of physical activity 29 . A cross-sectional study among medical residents in Brazil, indicated that long duty-hours were related to headache 30 . Long working hours were, however, not predictors of headache in two cohorts randomly drawn from the Norwegian 31 or Swedish 32 working populations.…”
Section: Discussionmentioning
confidence: 96%
“…Details and primary analyses of this study have already been published. 13,14 The questionnaire was outreached on social networks (Facebook and Instagram, in pages/profiles of medical residents' associations).…”
Section: Methodsmentioning
confidence: 99%